6(x-1)/9=4(x+1)/10

Simple and best practice solution for 6(x-1)/9=4(x+1)/10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)/9=4(x+1)/10 equation:



6(x-1)/9=4(x+1)/10
We move all terms to the left:
6(x-1)/9-(4(x+1)/10)=0
We calculate fractions
6x/()+(-(4(x+1)*9)/()=0
We calculate terms in parentheses: +(-(4(x+1)*9)/(), so:
-(4(x+1)*9)/(
We multiply all the terms by the denominator
-(4(x+1)*9)
We calculate terms in parentheses: -(4(x+1)*9), so:
4(x+1)*9
We multiply parentheses
36x+36
Back to the equation:
-(36x+36)
We get rid of parentheses
-36x-36
Back to the equation:
+(-36x-36)
We get rid of parentheses
6x/()-36x-36=0
We multiply all the terms by the denominator
6x-36x*()-36*()=0
We add all the numbers together, and all the variables
6x-36x*()=0

See similar equations:

| 12v+10v+14=8012v+10v+14=80. | | b=2(6)/3/2 | | 2/3a+-6=-24 | | 800-6m=100-10m | | x3=343 | | 3x+8=5xx= | | 24=11-10x | | -3m-2-m-7=19 | | .x3=343 | | 8x-9=3(x-4) | | 12x+10-15x=x-2-x | | 16-75=-3d+2 | | (3x+5)^1/3=-5 | | 2/7x+1/4=5/7x | | 136=-8-12x | | (x+8)/2=22 | | -9=-7-3x+1 | | (2x+7)^2=-25 | | -8h-15=-3(-2h+4) | | 2(3n-5)=-15 | | X(x-42)=180 | | 16t-(4t-6)=18 | | 2x2=14 | | 1.5x+13x=-84 | | 0.3x+0.6=0.5x-1.2 | | 1064=(20+x)*(30+x) | | 2x+4+3x=10 | | 3v^2+35v+49=8v | | 14-(2÷3)x=6 | | Y=x/(9x^2-4) | | (q+(-5)/3=8 | | 2/7x+1/4=1/3-5/7x+1/3 |

Equations solver categories